الوسائل الدبلوماسية لحلِّ النزاعات الدولية : دراسة حالة ( أزمة دارفور ) - محمد، محمد شعبان الجيلاني (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
Relations between countries are often characterized by conflicts and disagreements, which the international community seeks to find appropriate solutions to avoid or recur in the future, in addition to the establishment of controls for these relations between States, which works for the international institutions, particularly the United Nations, which aspires In order to avoid the difficulties and to create appropriate conditions for the resolution of conflicts and disputes in various ways and means to avoid resorting to force and violence that left devastation after two world wars in which human society suffered scourges and only poverty, underdevelopment and death. This is what we discussed through our study entitled "Diplomatic Means for Resolving International Conflicts - A Case Study of the Darfur Crisis", which attempts to discuss various peaceful means to resolve international conflicts, with research, description and analysis in the Darfur regional crisis and its local repercussions Region. To examine this, we divided the research into five main chapters, the last two chapters of which were devoted to the Darfur problem. We also highlighted the importance of diplomacy and its means in solving international disputes and the factors affecting them negatively and positively, with a focus on the emergence of conflict in the Darfur region and its causes and parties, and the role of international and regional organizations in reducing it. We have relied on our sources to gather information on previous relevant studies, and many Arab and foreign references and websites. In conclusion, we discussed most of the results achieved through this study, especially those relating to the various points that I saw important in the area of resolving international disputes by peaceful means, in addition to the proposed solutions and recommendations to resolve the Darfur regional crisis and its local repercussions. Expected to be resolved in the near future! Is there hope.